EXPERIENCED TEACHERS’ PERCEPTIONS: MATH-FOCUSED STEAM LEARNING - Dewi Rosikhoh; Liny Mardhiyatirrahmah; Abdussakir Abdussakir; Ahmad Abtokhi; Imam Rofiki (Abjadia, 2019)
Science, technology, engineering, arts, and mathematics (STEAM) have been applied in various countries because they have been able to answer the challenges of the globalization era. The implementation of STEAM at school has demanded that teachers have a role in making a relationship between disciplines in science contained in STEAM. The purpose of this research was to describe the perceptions of experienced teachers about math-focused STEAM learning. The research was a descriptive study on 14 vocational high school mathematics teachers in Malang, Indonesia. They had 20-30 years of teaching experience. Data were collected using essay questionnaires. The result showed that their perceptions of STEAM learning were positive. However, they also said that there were several obstacles to math-focused STEAM learning. The first obstacle was the unavailability of supporting literature. The second obstacle was that there were teachers who have no received training. The third obstacle was only a limited number of mathematics material that can be applied in STEAM learning. Additionally, the teacher stated that mathematics was more suitable as supporting contain in STEAM learning than as the primary focus.